2011
DOI: 10.4236/fns.2011.21003
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Dark Muscle from Yellowfin Tuna Thunnus albacares to Its Potential Application in the Food Industry

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 31 publications
0
15
0
5
Order By: Relevance
“…DM exhibited greater (P<0.05) TBARS values than LM at days 0 and 8 (Table 2), which can be attributed to dark muscle composition with large amount of total lipids, MUFA and myoglobin leading to faster lipid oxidation (SÁNCHEZ-ZAPATA et al, 2011). PETILLO et al (1998) reported that the great amount of lipid soluble antioxidants content in dark muscles was not enough to hinder the lipid oxidation process favored by the pro-oxidant activity of myoglobin due to the high content of this heme protein in dark muscles.…”
Section: Lipid Oxidationmentioning
confidence: 95%
See 1 more Smart Citation
“…DM exhibited greater (P<0.05) TBARS values than LM at days 0 and 8 (Table 2), which can be attributed to dark muscle composition with large amount of total lipids, MUFA and myoglobin leading to faster lipid oxidation (SÁNCHEZ-ZAPATA et al, 2011). PETILLO et al (1998) reported that the great amount of lipid soluble antioxidants content in dark muscles was not enough to hinder the lipid oxidation process favored by the pro-oxidant activity of myoglobin due to the high content of this heme protein in dark muscles.…”
Section: Lipid Oxidationmentioning
confidence: 95%
“…In accordance, researches in yellowtail (Seriola quinqueradiata), chub mackerel (Scomber japonicus), frigate mackerel (Auxis thazard), catfish (Clarias macrocephalus) and saithe (Pollachius virens) demonstrated that light and dark muscles of the same fish species present different composition and oxidative behavior (BAE & LIM, 2012;CHAIJAN et al, 2013;KARLSDOTTIR et al, 2014;SOHN et al, 2005). These facts can contribute for different color stability in these muscles, potentially interfering on the application in the food industry and the development of novel fish products (CHAIJAN et al, 2004;SÁNCHEZ-ZAPATA et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, en el atún enlatado, que incluye importantes cantidades de los túnidos tropicales aquí descritos, tan sólo se utiliza el 32-40% de la materia prima. Otra parte, correspondiente a la carne oscura (10-13%) se envasa en latas o bolsas como alimento para mascotas (Sánchez-Zapata et al 2011, FAO 2016a. Restaría por tanto casi otro 50% en el que se incluyen vísceras, espinas, estructuras óseas y escamas, que conllevan una mayor complejidad en su aprovechamiento.…”
Section: El Gran Reto De Este Siglo Para La Gestión Pesqueraunclassified
“…The high lipid content, less stable proteins, high concentration of heme proteins, lower pH values and higher concentration of sarcoplasmic proteins of dark flesh have been suggested to contribute difficulties in its fishery industry (Elena, et al, 2011). The characteristics of dark flesh, that make it not acceptable for fishery industry, are the strong dark color and the highly susceptibility to lipid oxidation speeding up its deterioration (Nishioka, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%